2013
DOI: 10.1016/j.ijheatmasstransfer.2013.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental investigation of a new film cooling geometry with high P/D ratio

Abstract: In order to improve the coolant surface coverage, in the past years new geometries have been proposed with higher lateral fan-shaped angle and/or greater inter-hole pitch distance (P/D). Unfortunately it is not possible to increase the fan angle or the pitch distance even further without inducing a coolant separation and a drop in the overall effectiveness.This study proposes an innovative design which improves the lateral coverage and reduces the jet lift off. The results have been validated by a combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…The authors' observed that the tilted stagnation line on the rotor leading edge moved from the pressure side to the suction side, and the instantaneous coolant streamlines shifted from the suction side to the pressure side with increasing rotational speed. The Reynolds-averaged Navier-Stokes equations closed by the k −ω SST turbulence model was used to investigate a film cooling geometry with high hole pitch to diameter ratio [21]. The experimental data was successfully reproduced using the CFD method.…”
Section: Miao and Chingmentioning
confidence: 99%
“…The authors' observed that the tilted stagnation line on the rotor leading edge moved from the pressure side to the suction side, and the instantaneous coolant streamlines shifted from the suction side to the pressure side with increasing rotational speed. The Reynolds-averaged Navier-Stokes equations closed by the k −ω SST turbulence model was used to investigate a film cooling geometry with high hole pitch to diameter ratio [21]. The experimental data was successfully reproduced using the CFD method.…”
Section: Miao and Chingmentioning
confidence: 99%
“…Montomoli vd. [20] fan-şekilli film soğutma deliği ile akış-üstü rampanın birlikte tasarımının FSE'ne etkisini incelemişlerdir. Yaptıkları çalışmada rampanın yanal yönle merkez çizgi boyunca yerel basınç farkı yarattığı ve bunun da jet akışkanın yanal yönde daha fazla yayılmasına yardımcı olduğunu belirtmişlerdir.…”
Section: Gi̇ri̇ş (Introduction)unclassified
“…Hammami et al 11 proposed a pyramidal slope structure based on the literature 10 and improved the coverage of the coolant on the wall. Montomoli et al 12 proposed a ramp structure that fits forward expansion holes and found that this structure can improve the spanwise average adiabatic film cooling efficiency of the forward expansion holes. Chen 13 experimentally studied an upstream ramp mounted on a row of film holes.…”
Section: Introductionmentioning
confidence: 99%